Electrical resistivity tomography for soil moisture estimation in terraced vineyards: a case study in the Douro Region, Portugal - Figueiredo, Tomás de (2022)
The Douro Region (Portugal), with an extension of ca. 43 000 ha of vineyards, is one of the most important wine regions in Europe and listed as a World Heritage site (UNESCO 2001). This is a supplementary reason for actions to preserve its natural resources such as soil and water. The regional topography exposes soils to severe erosion risk. In order to mitigate these risks, vineyards are installed in conservation structures typical of this area, called Terraços or Socalcos (Terraces). These structures require important earth movement to secure them properly which results in strong disturbance of soil structure and soil water movement. The aim of this study is to compare soil water content of a terraced vineyard in the wet season (January) with that in the dry season (July), using Electrical Resistivity Tomography (ERT). ERT has been broadly used to assess soil water moisture, also in vineyards. However, in this case it is necessary to take into account the complex topography of the terraces in order to obtain a reliable soil profile model. The study was carried out in a terraced vineyard at Peso da Régua. ERT transects were measured in three neighbouring areas of the vineyard: Terrace, Inter-terrace and Terrace. Transects in the Terrace areas were parallel to the slope while transects in the Inter-terrace area were perpendicular to the slope. Six transects were carried out (three in January and three in July in the same positions). Electrode spacing along the 20 m transects was 0.5 m. Also, soil samples were taken at 4 depths (0.0 - 0.5 m; 0.5 - 0.10 m; 0.10 - 0.20 m; >0.20 m) for gravimetric water content determination. ERT data obtained were inverted taking into account the topography, to obtain soil electrical resistivity profiles. For this case study, ERT results provided an adequate representation of soil moisture profiles, offering possibilities of fast and detailed appraisal of soil water content and distribution in terraced vineyards.